BAHASA INDONESIA DALAM WACANA PROPAGANDA POLITIK KAMPANYE PEMILU 2009 SATU KAJIAN SOSIOPRAGMATIK - Tri Sulistyaningtyas (Fakultas Seni Rupa dan Desain ITB, 2009)
The analysis of implicatures made by the legislative candidates in the campaign billboards and banners shows that these two media are basically used for their political struggles. The campaign language in the media is used as an instrument for the candidates to create their good images to win the public's sympathies. To understand the implicatures of their campaign discourses, the public should understand the contextual background in which the implicatures are made. These implicatures are more suitably categorized as both their illocutionary and perlocutionary acts whose purpose are to persuades the public to vote for them, while taking into account their practical use